Impact of an intermittent exercise fatique protocol on biomechanic indicators for strength and accuracy of soccer penalty kick - Mohammed, A. H. A. (Serbian Journal of Sports Sciences, 2009)
The purpose of this study was to examine the effectiveness of intermittent exercise fatigue on certain biomechanical indicators for accuracy and strength of penalty kicks in soccer players. Six soccer players volunteered to participate. Each player shot 24 penalty kick trials, 8 trials every 15 minutes for three times after the physical fatigue protocol. The goal was divided into four rectangles, two at the upper corners right and left, and the other two in lower corners right and left. Each player shot inside the upper right rectangle, followed by the lower right, the upper left, and the lower left, with two shoots per each rectangle. All trials were treated by a 3-dimensional mechanical analysis using Simi Motion Program. The results showed that the fatigue protocol affected the vertical displacement of corridor Z-axis in the right toe and the right heel. There is a relation between fatigue and the amount of force in penalty kicks shooting. The best vertical distance for the kicking foot at the moment of impact is 7 centimeters from beneath the ball center for the heel, 3 centimeters for the toe, and 6.5 centimeters for the knee.